UPAYA PEMBERANTASAN ILLEGAL, UNREPORTED AND UNREGULATED (IUU) FISHING DI LAUT ARAFURU PADA MASA PEMERINTAHAN PRESIDEN JOKO WIDODO - Tyas Retno Kusumaningsih Setyasih Harini, GPH. Dipokusumo (Solidaritas, 2018)
ABSTRACTThis study aimed to address the attempt of eradicating Illegal, Unreported, and Unregulated (IUU) Fishing in Arafuru Sea during President Joko Widodo’s reign. This research was intended to find out how Indonesia’s attempt is in eradicating IUU Fishing during President Joko Widodo’s reign. Indonesia’s strategic condition with abundant resource in fishing sector encounters very significant decrease in fish stock; it is because the illegal fishing commonly occurring in Indonesian broad waters. The threats coming from foreign ships disrupt Indonesian maritime sovereignty and security. This research was conducted using geopolitical theory related to geostrategy and maritime security. The research method employed in this study was a qualitative research method. The data used was secondary data. Techniques of collecting data used were documentation and library study with descriptive elaboration. From the analysis on the attempt of eradicating Illegal, Unreported, and Unregulated Fishing in Arafuru Sea during President Joko Widodo’s reign, the author found that the Policy of Eradicating Illegal, Unreported, and Unregulated Fishing during President Joko Widodo’s reign included establishing Task Force 115 in securing the sea, developing Minister’s Regulation No.56 of 2014 about moratorium of ex-foreign ship license, Minister Regulation No.57 of 2014 prohibiting the transshipment in the mid of sea. Those policies were very optimal thereby relieving Indonesian waters area from illegal foreign ships. Keywords: Illegal, Unreported, and Unregulated Fishing, maritime security, Arafuru Sea